EVALUATION OF THE AVAILABILITY OF OUTDOOR SPACE TO SUPPORT EDUCATION AND ACTIVITIES AT THE DARUL FALLAH AGRICULTURAL ISLAMIC BOARDING SCHOOL, BOGOR - Ghaitsa Jannata; Simangunsong, Nur Intan; Fitri, Rini (Journal of Synergy Landscape, 2024)
-